Study of dropout in undergraduate degree in chemistry teaching at IFMA – São Luís Monte Castelo campus (Research, Society and Development, 2022)
Student dropout has been a concern for higher education institutions in Brazil and worldwide. Aiming to understand the student dropout in the Undergraduate Chemistry course of IFMA-Monte Castelo, we analyzed the classes from 2002 to 2018. A descriptive and analytical methodology was used, addressing quanti and qualitatively data obtained from the academic system and questionnaires applied. For the classes of 2002 to 2018, the class of 2003 had the highest number of graduates (74%) and the lowest number of dropouts (26%). The highest evasion occurred in the class of 2006 (84%) and the class of 2010 had the lowest number of graduates (9%). For the classes of 2014 to 2018, the 2014 class had the highest evasion (77%) and the 2018 class had the lowest (7%). Financial hardship, moving to a different county/distance, children, and employment led to student dropout. To prevent and combat dropout, the institution should monitor and guide students, as well as increase the number of scholarships.